Comparative Historical Analysis Of The Development Of Creativity In Primary School Education - Dauletmuratova Bayramgul Maxsetbay qızı (Genius Journals, 2025)
This article examines the historical evolution of approaches to fostering creativity in primary education. From classical didactic models to modern constructivist theories, the nurturing of creativity has undergone profound transformations. Drawing on a range of historical and contemporary sources, this study identifies key stages in the conceptualization of creativity, evaluates the impact of pedagogical innovations, and highlights the evolving understanding of the child's creative potential. The analysis reveals a gradual shift from rote learning toward student-centered, activity-based models that recognize creativity as a critical component of holistic development.
Keywords: creativity; primary education; historical analysis